Lack of Synergy of Erythromycin Combined with Penicillin or Cefotaxime against Streptococcus pneumoniae In Vitro - Lin, Eugene (American Society for Microbiology, 2003)
We investigated a possible synergistic effect of a macrolide and β-lactams against Streptococcus pneumoniae strains with different resistance profiles. Checkerboard and time-kill assays of erythromycin combined with penicillin or cefotaxime essentially showed indifference, suggesting that these antibiotics in combinations in vitro act substantially as individuals in their activity against S. pneumoniae.